Humoral Immunogenicity of the mRNA-1273 Vaccine in the Phase 3 Coronavirus Efficacy (COVE) Trial. (10th May 2022) - El Sahly, Hana M; Baden, Lindsey R; Essink, Brandon; Montefiori, David; McDermont, Adrian; Rupp, Richard; Lewis, Michael; Swaminathan, Shobha; Griffin, Carl; Fragoso, Veronica; Miller, Vicki E; Girard, Bethany; et al.
Abstract: Background: Messenger RNA (mRNA)–1273 vaccine demonstrated 93.2% efficacy against coronavirus disease 2019 (COVID-19) in the Coronavirus Efficacy (COVE) trial. The humoral immunogenicity results are now reported. Methods: Participants received 2 mRNA-1273 (100 µg) or placebo injections, 28 days apart. Immune responses were evaluated in a prespecified, randomly selected per-protocol immunogenicity population (n = 272 placebo; n = 1185 mRNA-1273). Serum binding antibodies (bAbs) and neutralizing antibodies (nAbs) to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–spike protein were assessed at days 1, 29, and 57 by baseline SARS-CoV-2–negative (n = 1197) and SARS-CoV-2–positive (n = 260) status, age, and sex. Results: SARS-CoV-2–negative vaccinees had bAb geometric mean AU/mL levels of 35 753 at day 29 that increased to 316 448 at day 57 and nAb inhibitory dilution 50% titers of 55 at day 29 that rose to 1081 at day 57. In SARS-CoV-2–positive vacinees, the first mRNA-1273 injection elicited bAb and nAb levels that were 11-fold (410 049) and 27-fold (1479) higher than in SARS-CoV-2–negative vaccinees, respectively, and were comparable to levels after 2 injections in uninfected participants. Findings were generally consistent by age and sex. Conclusions: mRNA-1273 elicited robust serologic immune responses across age, sex, and SARS-CoV-2 status, consistent with its high COVID-19 efficacy. Higher immune responses in those previously infected support a booster-type effect. Clinical Trials Registration. NCT04470427. Abstract : mRNA-1273 elicited robust humoral immunogenicity in a subset of participants of the phase 3 COVE study across age, sex, and baseline SARS-CoV-2 status, consistent with its high COVID-19 efficacy. Higher immune responses in those previously infected with SARS-CoV-2 support a booster-type effect.